2018
DOI: 10.3390/su10072431
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Particle Matter Dry Deposition on Green Roofs and Living Walls Vegetation for Mitigating Urban Atmospheric Pollution in Semiarid Climates

Abstract: Abstract:In the last two decades, the incorporation of green roofs and living walls in buildings has increased significantly worldwide because of their benefits such as building energy savings, promoting biodiversity, controlling water run-off, mitigating urban heat island effect, improving indoor and urban air quality, and connecting people with nature. However, few studies have quantified the impact of green roofs (GRs) and living walls (LWs) on mitigating air pollution, especially in semiarid climates where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(29 citation statements)
references
References 35 publications
(84 reference statements)
0
29
0
Order By: Relevance
“…Epicuticular wax ultrastructures were also found to be significant in PM deposition to both conifers and broadleaves by a number of other studies 36,90,103,113 . Grote et al 77 suggest that this may be partly due to leaf wettability, with particle concentrations significantly reduced through reactions with wet surfaces, and water-soluble pollutants such as NO 2 and SO 2 subject to dissolution in a water film at the leaf surface.…”
Section: Leaf Surface Featuresmentioning
confidence: 68%
See 2 more Smart Citations
“…Epicuticular wax ultrastructures were also found to be significant in PM deposition to both conifers and broadleaves by a number of other studies 36,90,103,113 . Grote et al 77 suggest that this may be partly due to leaf wettability, with particle concentrations significantly reduced through reactions with wet surfaces, and water-soluble pollutants such as NO 2 and SO 2 subject to dissolution in a water film at the leaf surface.…”
Section: Leaf Surface Featuresmentioning
confidence: 68%
“…Leaf size and shape or complexity Differences in leaf size and complexity are significant predictors of deposition, particularly for PM 91 . Numerous field experiments have found that species with smaller leaves tend to be more effective than species with larger leaves, which may be partly attributed to the higher perimeter/surface area ratio of smaller leaves 103 . For example, a recent study into leaf characteristics for traffic-related PM (PM 1 , PM 2.5 and PM 10 ) capture found that leaf size inversely correlated with PM accumulation, whereas there were no leaf surface characteristics that showed a clear correlation with PM accumulation across species 104 .…”
Section: Density and Porositymentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical data from a survey on the perception of local people and employees of the VGS installed on one office building in Genoa, Italy revealed that people see VGS as effective tools to improve air quality and the urban environment [68]. Another empirical study by Viecco et al [69] aimed to quantify the dry deposition of particle matters by vegetation species (Pitosporumtobira, Lavandulaangustifolia, Lampranthusspectabillis, Sedumalbum, and Sedumreflexum) in semiarid climates. The species with the highest potential to capture particle matter were S. album, S. reflexum, S. palmeri, and L. spectabillis.…”
Section: Reduction Of Air Pollutionmentioning
confidence: 99%
“…Particulate removes of the atmosphere through washing by rainwater and deposites due to gravity settling or an object such as a plant. Some plant specieses have a good ability to deposite particulate for reducing particulate in urban ambient air (Viecco et al, 2018). The smaller the particle size the greater the viscosity force so that it becomes more difficult to settle in the ground.…”
Section: Most Of Centralmentioning
confidence: 99%